2017
DOI: 10.1007/s11557-017-1311-3
|View full text |Cite
|
Sign up to set email alerts
|

Resurrection and emendation of the Hypoxylaceae, recognised from a multigene phylogeny of the Xylariales

Abstract: A multigene phylogeny was constructed, including a significant number of representative species of the main lineages in the Xylariaceae and four DNA loci the internal transcribed spacer region (ITS), the large subunit (LSU) of the nuclear rDNA, the second largest subunit of the RNA polymerase II (RPB2), and beta-tubulin (TUB2). Specimens were selected based on more than a decade of intensive morphological and chemotaxonomic work, and cautious taxon sampling was performed to cover the major lineages of the Xyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
191
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 162 publications
(212 citation statements)
references
References 87 publications
(89 reference statements)
19
191
0
2
Order By: Relevance
“…Species in this genus constitute a rich source of bioactive secondary metabolites (Song et al 2014). Recently the phylogeny of the family was changed, following multilocus DNA pyhlogenies and some comprehensive reviews of their taxonomy have been provided by Daranagama et al (2018) and Wendt et al (2018). Helaly et al (2018) concluded that future culturing and phylogenetic studies are needed to reach a better taxonomic classification of Xylaria.…”
Section: Xylaria Hill Ex Schrankmentioning
confidence: 99%
“…Species in this genus constitute a rich source of bioactive secondary metabolites (Song et al 2014). Recently the phylogeny of the family was changed, following multilocus DNA pyhlogenies and some comprehensive reviews of their taxonomy have been provided by Daranagama et al (2018) and Wendt et al (2018). Helaly et al (2018) concluded that future culturing and phylogenetic studies are needed to reach a better taxonomic classification of Xylaria.…”
Section: Xylaria Hill Ex Schrankmentioning
confidence: 99%
“…ex Lindau. This genus is included in the Graphostromataceae (Xylariales) and is characterized by the presence of macronematous conidiophores, usually forming a vesicle clavate at the apex, where cicatrized, sympodial conidiogenous cells produce unicellular, hyaline conidia with rhexolytic secession (Seifert et al 2011;Wendt et al 2018). Xylocladium claviforme was first described as Masoniomyces claviformis J.L.…”
Section: Dactylaria Biguttulatamentioning
confidence: 99%
“…The genus Daldinia was described by Cesati and De Notaris (1863) and belongs to the Hypoxylaceae (Xylariales), since the recent rearrangement of the families of stromatic Xylariales by Wendt et al (2018). The Hypoxylaceae is one of the largest families in this order and both the family and the genus Daldinia have been studied exhaustively for secondary metabolite production (Helaly et al 2018).…”
Section: Introductionmentioning
confidence: 99%